Implementasi Moderasi Islam di Tengah Pluralisme Agama Dimensi Sosial di Ngoro Jombang - Fatikah, Noor; Mujahidin, Mujahidin; Rozak , Abd.; Nurussoba, Wiwin; Rofiq, Ainur (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
This community service aims to identify and strengthen the practice of Islamic moderation in the pluralistic community of Sedati Hamlet, Kauman Village, Ngoro Subdistrict, Jombang Regency. The main focus is on how the values of tolerance and mutual respect can be applied in the context of religious and cultural diversity. This activity uses an empirical approach with a qualitative descriptive design. Data collection techniques include in-depth interviews with religious leaders and residents, direct observation in the community, and documentation of religious and social activities. The results of this community service show: (a) The community of Sedati Hamlet has implemented Islamic moderation values through tolerant attitudes and rejection of extreme actions, such as regulating the use of loudspeakers during worship and respecting the practice of other religions; (b) Religious pluralism is reflected in the harmonious social life between Muslims (both Nahdlatul Ulama and LDII) and Protestant Christians, who each have their places of worship and live together peacefully; (c) The role of religious leaders and village officials is highly significant in maintaining interfaith harmony, with full support from the village head, local police station, and military post. This dedication contributes to strengthening a community model based on religious moderation, which can serve as a reference for building a peaceful and tolerant social order amidst diversity